Strategi Sekolah dalam Menginternalisasikan Nilai Karakter Gotong Royong pada Siswa di SMP Negeri 1 Prambon Nganjuk - Vivi Mustaghfiroh; Listyaningsih Listyaningsih (Kajian Moral dan Kewarganegaraan, 2023)
This study aims to describe school strategies, supporting factors, and obstacles in internalizing the value of the gotong royong character in students at SMP Negeri 1 Prambon Nganjuk. This type of research is qualitative with descriptive method. The theory used in this research is Thomas Lickona's theory of character education. The focus of this paper is on the school's strategy in internalizing the value of the gotong royong character, knowing the supporting and inhibiting factors for internalizing the value of the gotong royong character and its solutions. Data collection techniques using observation, guided free interviews, which are a combination of free interviews and guided interviews, and documentation. The results showed that the school strategy in internalizing the value of the gotong royong character in students at SMP Negeri 1 Prambon Nganjuk was carried out through: (1) classroom learning guided by the teaching module, (2) co-curricular activities, (3) exemplary, (4) habituation. Supporting factors in internalizing the value of the gotong royong character in students at SMP Negeri 1 Prambon include: the availability of supporting facilities and infrastructure in internalizing the value of the gotong royong character, the potential of the school, good commitment and motivation from teachers and students, there are school activities that support the internalization of gotong royong. The inhibiting factors for the internalization of the value of the gotong royong character in students at SMP Negeri 1 Prambon include: different student characteristics, lack of student commitment and motivation in doing mutual cooperation, there are still teachers who have low awareness and concern for student character. Keywords: strategy, school, mutual cooperation character values